Сonversation with Сomrade Whitman (Rumeau, Delphine. Comrade Whitman: From Russian to Internationalist Icon. Boston: Academic Studies Press, 2024.) - Tatiana D. Venediktova (Литература двух Америк)
The review discusses Delphine Rumeau’s book Comrade Whitman: From Russian to Internationalist Icon (2024) — itself a discussion of the Russian and Soviet “uses” of Walt Whitman in the 20th century. Whitman initially impressed Russian intellectuals as a “cosmic” mystical seer, but following the 1917 revolution he was transformed into a social icon, politically correct because associated with communist internationalism and of stature in what was soon to become the “Third World” and “The Left” in Europe and USA. It seems obvious that for a poet to be appropriated by an ideology (whether communist, socialist, or liberal) entails both costs and benefits: “comrade Whitman” for one grew into a popular figure influence that tended to be quite monochrome and was viewed in a highly selective perspective. The question brought up in the discussion is this: was Whitman’s Russian career, indeed, aborted when Soviet ideology came to an end in the 1980s (which Delphine Rumeau’s study seems to imply) or would his post-Soviet fortunes in Russia become more visible if we use a different type of cultural transfer optics?